ANÁLISE DO NÍVEL DE SEDENTARISMO RELACIONADA À ATIVIDADE FÍSICA NA PROMOÇÃO DA SAÚDE DOS POLICIAIS MILITARES DO 3º BATALHÃO DE POLÍCIA MILITAR DO ESTADO DO ACRE (Fiep Bulletin - online, 2024)
The scope of this scientific article is intrinsically focused on seeking a systematic analysis regarding the level of sedentarism of the military policemen crowded in the 5th Military Police Battalion of the State of Acre, located in the city of Rio Branco, the capital of this State. With this, we elaborated a methodical research from a questionnaire with questions that express the relationship of the military policemen, in question, with the practice of the physical activity to the detriment of a sedentary and hypokinetic behavior. Finally, we performed an analysis of the data obtained through graphs resulting from the questions raised in this research, as well as highlighting the relevance of Physical Education Professionals in a Military Police Battalion.